Redesigning developmental education: a comparative study - Fuller, Paula Dean (Kansas State University, 2024)
Developmental Education reform has been a vital topic in the field of higher education for decades. There have been several initiatives to further engage under-prepared college students and move them through gateway courses like freshman-level English and Math. One of the more emergent instructional models is referred to as co-requisite instruction. This method allows for students to be co-enrolled in a developmental course and a gateway, freshmen-level course simultaneously. The state of Texas instituted this practice under House Bill 2223 for all public, higher education institutions. The researcher sought to compare student success rates and persistence for students enrolled in co-requisite English courses to those enrolled in traditional, freshman-level English. Using data from an institution that will be referred to as Southeast Texas Community College, the study revealed that there were only a few areas where there were statistically significant differences in the outcomes. However, the results were still rather encouraging and tell the story of additional measures that should be explored to continue to improve student success through institutional, programmatic, and instructional reform.
Keywords: Corequisites; Developmental education; Community colleges; Remedial courses